Influence of egg pre-storage heating period and storage length on incubation results - Silva, F. H. A.; Faria, D. E.; Torres, K. A. A. [UNESP]; Faria Filho, D. E.; Coelho, A. A. D.; Savino, V. J. M. (Fundação APINCO de Ciência e Tecnologia Avícolas, 2008)
This experiment aimed at evaluating the influence of different heating times of settable eggs of Cobb 500® broiler breeders before submitting them to different storage periods on egg weight loss, embryo mortality, and hatchability. A total number of 1,980 eggs were distributed in a completely randomized experimental design with a 3 x 3 factorial arrangement, comprising nine treatments with 22 replicates of 10 eggs each. The following factors were analyzed: pre-storage heating periods (0, 6, 12 hours at 36.92°C) and storage periods (4, 9, 14 days at 12.06°C). After storage, eggs were incubated under usual conditions, and were transferred to the hatcher at 442 hours of incubation. Eggs were weighed before heating, incubation, and transference to determine weight loss. Partial hatchability was determined at 480 hours, and total hatchability at 498 hours of incubation. Embryo mortality was determined in non-hatched eggs. It was concluded that heating eggs for six hour before storage improves incubation results as it decreases incubation length and late embryo mortality, therefore its use can be indicated in commercial operations. Storing eggs for 14 days and pre-heating for 14 days and pre-heating for 12 hours severely impair incubation results, and therefore are not recommended.
Keywords: Broiler breeders; egg weight loss; embryo development; embryo mortality; hatch